Vinganças, guerras e retaliações: um estudo sobre o conteúdo moral dos homicídios de caráter retaliatório nas periferias de Belo Horizonte - Rafael Lacerda Silveira Rocha (2017)
This thesis deals with the moral content of homicides resulting from retaliatory dynamics in peripheral neighborhoods in the eastern zone of Belo Horizonte. These deaths have a moral nature, since they are associated with the notion of search for justice, albeit privately and violently. Of special interest are the homicide chains, revenge and retaliation cycles between groups, popularly called wars, in which each aggression serves as a justification for subsequent killings. Based on interviews with residents of three neighborhoods in the eastern zone of Belo Horizonte and the analysis of the police inquiries regarding homicides committed in those localities, I sought to understand how these deaths are linked, and the ways in which the actors involved articulate their justifications and narratives, to understand the mechanisms, moral content that allow the murders to be used as a mean to redress against an offense or aggression. For this, the notion of a moral grammar of crime was mobilized, a set of elements consisted of practices, values, sociabilities, norms, prohibitions and typologies that are repeated regularly in the relations between actors involved with groups and criminal practices in favelas and poor neighborhoods. From this notion, I sought to explore how these moral elements are articulated and operationalized in different contexts, often in conflicting ways. I discuss the role of mediators, who operate in the face of these disputes between actors inserted in the local criminal dynamics, and their limitations, in a scenario as fragmented and dispersed as the peripheral neighborhoods and favelas of Belo Horizonte, where innumerable armed groups coexist in relationships marked by distrust or declared conflict. Finally, I explore the relationships between the processes of structuring groups and criminal activities, the existence of a third mediator, the possibilities of articulating the moral grammar of crime, and controlling the cycles of revenge and retaliation among its participants.